Collagenic architecture and morphotraits in a marine basal metazoan as a model for bioinspired applied research. (26th February 2022) - Manconi, Renata; Cubeddu, Tiziana; Pronzato, Roberto; Sanna, Marina A.; Nieddu, Gabriele; Gaino, Elda; Stocchino, Giacinta A.
Abstract: In some Porifera (Demospongiae: Keratosa), prototypes of the connective system are almost exclusively based on collagenic networks. We studied the topographic distribution, spatial layout, microtraits, and/or morphogenesis of these collagenic structures in Ircinia retidermata (Dictyoceratida: Irciniidae). Analyses were carried out on a clonal strain from sustainable experimental mariculture by using light and scanning electron microscopy. Histology revealed new insights on the widely diversified and complex hierarchical assemblage of collagenic structures. Key evolutionary novelties in the organization of sponge connective system were found out. The aquiferous canals are shaped as corrugate‐like pipelines conferring plasticity to the water circulation system. Compact clusters of elongated cells are putatively involved in a nutrient transferring system. Knob‐ended filaments are characterized by a banding pattern and micro‐components. Ectosome and outer endosome districts are the active fibrogenetic areas, where exogenous material constitutes an axial condensation nucleus for the ensuing morphogenesis. The new data can be useful to understand not only the evolutionary novelties occurring in the target taxon but also the morpho‐functional significance of its adaptive collagenic anatomical traits. In addition, data may give insights on both marine collagen sustainable applied researches along with evolutionary and phylogenetic analyses, thus highlighting sponges as a key renewable source for inspired biomaterials. Therefore, we also promote bioresources sustainable exploitation with the aim to provide new donors of marine collagen, thereby supporting conservation of wild populations/species. Abstract : A prototype of connective system, almost exclusively based on collagenic networks, is zoomed in the model sponge Ircinia retidermata (Porifera: Keratosa). We focused on topographic distribution, spatial layout, microtraits, and/or morphogenesis of these collagenic structures. Ectosome and outer endosome are the active fibrogenetic areas where exogenous inorganic material is a key condensation nucleus for the ensuing morphogenesis of main skeleton. Corrugate‐like pipelines of the aquiferous canals conferring plasticity to the water circulation system, cell clusters competent for nutrient transfer, knob‐ended filaments with a banding pattern and micro‐components herein represent key evolutionary novelties in the organization of sponge connective system.